Síntese, caracterização e avaliação do potencial fotossensibilizador de nanopartículas do polímero conjugado PCPDTBT visando a fotoinativação de bactérias - THALÍTA HELLEN NUNES LIMA (2023)
Antimicrobial resistance is one of the main actual global health challenges. It is estimated that if no action is taken in present, the number of deaths from resistant bacteria will be of 10 million dollars per year in 2050. Furthermore, antimicrobial resistance would economic losses, which can reach 100-210 trillion dollars by 2050. In this scenario, conjugated polymers have shown excellent optical properties. The conjugated polymer poly[2,6-(4,4-bis-(2-Ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b′]dithiophene)-alt-4,7(2,1,3benzothiadiazole)]-PCPDTBT has been used as a photoactivatable agent in photothermal therapy of cancer cells. However, the fact that PCPDTBT is not soluble in water makes the use of this polymer a challenge for most biomedical applications.. The main challenge related to the use of PCPDTBT in biomedicine is the fact that it is not a water-soluble polymer. Hence, this work aimed to synthesize, characterize and apply PCPDTBT nanoparticles (PCPDTBT-NPs) in the photoinactivation of bacteria. We prepared nanoparticles from PCPDTBT through nanoprecipitation methods using amphiphilic stabilizing agents (Tween 20). For the assessment of the biological activity, the gram-negative bacteria Escherichia coli (E. coli) and the gram-positive bacteria Staphylococcus aureus (S. aureus) were used. The strain was incubated with the PCPDTBT-NPS for 1 h and then exposed to two treatments that were (i) irradiated and (ii) kept in the dark. The irradiated groups were exposed to white, red, green and blue light. To unravel the photoinactivation mechanisms, experiments were carried out to evaluate the production of reactive oxygen species using the fluorescent probe DCFHDA and the thermal effects of irradiation were also studied. In the irradiated group, the bacteria were subjected to white, red, green and blue light, for 90 min. PCPDTBT-NPs presented an average hydrodynamic diameter of 140.2 nm and a mild electropositive zeta potential (2,03±3,98 mV). The PCPDTBT-NPs showed absorption peaks at 408 and 655 nm, while the fluorescence emission showed bands in the region of 400-500 nm and 600-800 nm. The PCBTBT-NPs did not show bactericidal effects for the dark group, however, the samples that were exposed to white light presented a photobactericidal effect against E. coli. The generation of ROS was observed for all irradiation conditions. On the other hand, only white light produced significant heat for the context of photothermal therapy. Therefore, the results suggest that PCPDTBT-NPs are promising materials to be used to photoinactivate bacteria through the combined action of ROS and heat generation.